2021
DOI: 10.1080/21505594.2021.1888458
|View full text |Cite
|
Sign up to set email alerts
|

Domain in Fiber-2 interacted with KPNA3/4 significantly affects the replication and pathogenicity of the highly pathogenic FAdV-4

Abstract: The outbreaks of hepatitis-hydropericardium syndrome (HPS) caused by the highly pathogenic serotype 4 fowl adenovirus (FAdV-4) have caused a huge economic loss to the poultry industry globally since 2013. Although the Fiber-2 has been identified as a key virulent related factor for FAdV-4, little is known about its molecular basis. In this study, we identified the efficient interaction of the Fiber-2 with the karyopherin alpha 3/4 (KPNA3/4) protein via its N-terminus of 1–40aa. The analysis of the overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
0
26
1
Order By: Relevance
“…Fiber-1 and Fiber-2 play vital roles in mediating the infection and pathogenesis of FAdV-4, respectively. Recently, studies by our group and other groups found that Fiber-1, not Fiber-2, directly triggered the viral infection of FAdV-4 ( 4 , 5 ), whereas Fiber-2 and Hexon, but not Fiber-1, were the virulence determiners for the highly pathogenic FAdV-4 in comparison with the nonpathogenic strain ( 6 8 ). Notably, as one of the capsid proteins of FAdV-4, Fiber 2 has been identified as an efficient protective immunogen for subunit vaccine candidates ( 9 ).…”
Section: Introductionmentioning
confidence: 85%
“…Fiber-1 and Fiber-2 play vital roles in mediating the infection and pathogenesis of FAdV-4, respectively. Recently, studies by our group and other groups found that Fiber-1, not Fiber-2, directly triggered the viral infection of FAdV-4 ( 4 , 5 ), whereas Fiber-2 and Hexon, but not Fiber-1, were the virulence determiners for the highly pathogenic FAdV-4 in comparison with the nonpathogenic strain ( 6 8 ). Notably, as one of the capsid proteins of FAdV-4, Fiber 2 has been identified as an efficient protective immunogen for subunit vaccine candidates ( 9 ).…”
Section: Introductionmentioning
confidence: 85%
“…Since the outbreak of HHS caused by novel FAdV-4, in 2015, several candidate vaccines have been reported [19]. However, few live attenuated vaccines based on the emerging novel FAdV-4 have been evaluated [17,18]. We previously generated a non-pathogenic chimeric virus rHN20 by replacing the hexon gene of the FAdV-4 virulent strain HLJFAd15 with that of the non-pathogenic strain ON1 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Live attenuated FAdV-4 have been produced by passaging virulent FAdV-4 in chicken embryos [14] or QT35 cells [15,16], but the protective effect of these attenuated vaccines on the emerging FAdV-4 is also unknown. Recent studies revealed that recombinant viruses generated from novel genotype FAdV-4 strain in which enhanced green fluorescent protein (EGFP) was fused to the N-terminus of fiber-2 gene or in which the N-terminus of fiber-2 was knocked out was not pathogenic to specific pathogen-free (SPF) chickens, but the titers of the recombinant viruses were significantly lower in vitro than those of wild-type FAdV-4 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we used CRISPR-Cas9 technique to target the virulent gene fiber-2 to generate two live-attenuated fiber-2 -edited vaccine candidates FA4-EGFP and FAV-4_Del ( 7 , 8 ). In this study, we targeted another structural protein Fiber-1 of FAdV-4 to rescue a novel recombinant virus FAdV4-RFP_F1 expressing the fusion protein of RFP and Fiber-1.…”
Section: Discussionmentioning
confidence: 99%
“…Different from most serotypes of FAdV, FAdV-4 has two Fiber proteins, designated as Fiber-1 and Fiber-2 (5). Recently, Fiber-2 was identified to be closely related with the virulence of FAdV-4, and the fiber-2-edited recombinant viruses FA4-EGFP and FAV-4_Del were highly attenuated to the SPF chickens (6)(7)(8). Notably, Fiber-1, but not Fiber-2, was identified to directly trigger viral infection via its knob and shaft domain through the cellular receptor, the CAR homology (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%